Penggunaan AHP guna penentuan prioritas penanganan permukiman tangguh bencana longsor - Sri Utami; Kartika Ekasari; Ramadhan Mayzer Saputra (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
The 2010-2030 Batu City Spatial Plan states that the area with a high risk of landslides in Batu City is located in Temas Village. Risks with the threat of landslides are "high", social vulnerability is "medium" and economic vulnerability is "high". In order to determine the priority for handling landslide resilient settlements, the Analytical Hierarchy Process (AHP) method is the most relevant. The purpose of this research was to determine the priority for handling disaster resilient settlement elements. The tool used was a pairwise comparison questionnaire. Settlement-forming elements namely nature, man, society, shell and network. However, this research was focused on the field of architecture namely shell (foundation, building shape, structural design, location, roof) and network (roads, clean water, drainage, dirty water, solid waste). The results showed that the priority order for handling landslide resilient settlements from shell elements namely building foundations, location and structure of buildings. Meanwhile, the network elements were started from environmental drainage, roads and clean water.